Compliance with family planning and its association with quality of life among Meranaw women in rural Philippines - Maslainie Aliola; Hamdoni Pangandaman (Public Health and Occupational Safety Journal, 2026)
Background: The COVID-19 pandemic disrupted access to essential health services, including family planning (FP), particularly in rural and underserved communities. These disruptions may influence women’s reproductive practices and overall quality of life (QoL). Objectives: This study aimed to determine the level of family planning compliance and examine its influence on the quality of life among Meranaw women during the COVID-19 pandemic. Methods: A descriptive cross-sectional design was employed among 378 Meranaw women who were family planning users in selected municipalities of Lanao del Sur, Philippines. Data were collected from January to October 2022. A stratified random sampling technique was used based on municipal distribution to ensure proportional representation of respondents. A validated researcher-developed questionnaire assessed attitude- and practice-related compliance (CVI = 0.81–0.92; α = 0.79), while QoL was measured using the WHOQOL-BREF. Data were analyzed using descriptive statistics and multiple linear regression. Results: Respondents demonstrated high compliance in both attitude (mean = 3.61) and practice (mean = 3.41) domains. Overall QoL was rated very satisfactory (mean = 5.72), with the highest scores in the psychological (mean = 5.89) and relational (mean = 5.85) domains. Multiple regression analysis revealed that age (β = .319, p < .001), monthly income (β = –.097, p = .008), number of children (β = .395, p < .001), duration of FP use (β = .092, p = .034), and type of FP method (β = .129, p < .001) significantly predicted QoL. The model explained a substantial proportion of variance (R² = 0.974), indicating strong predictive capacity. Conclusions: Meranaw women demonstrated high compliance with family planning practices despite pandemic-related constraints, thereby significantly improving the quality of life. Sustaining family planning services during public health crises is essential to maintaining women’s well-being, particularly in rural and culturally distinct populations.